Comparison of modeling methods and parametric study for a piezoelectric wind energy harvester - Zhao, Liya (2014)
Harvesting flow energy by exploiting transverse galloping of a bluff body attached to a piezoelectric cantilever is a prospective method to power wireless sensing systems. In order to better understand the electroaeroelastic behavior and further improve the galloping piezoelectric energy harvester (GPEH), an effective analytical model is required, which needs to incorporate both the electromechanical coupling and the aerodynamic force. Available electromechanical models for the GPEH include the lumped parameter single-degree-of-freedom (SDOF) model, the approximated distributed parameter model based on Rayleigh–Ritz discretization, and the distributed parameter model with Euler–Bernoulli beam representation. Each modeling method has its own advantages. The corresponding aerodynamic models are formulated using quasi-steady hypothesis (QSH). In this paper, the SDOF model, the Euler–Bernoulli distributed parameter model using single mode and the Euler–Bernoulli distributed parameter model using multi-modes are compared and validated with experimental results. Based on the comparison and validation, the most effective model is employed for the subsequent parametric study. The effects of load resistance, wind exposure area of the bluff body, mass of the bluff body and length of the piezoelectric sheets on the power output are investigated. These simulations can be exploited for designing and optimizing GPEHs for better performance.